2021
DOI: 10.1093/cid/ciab032
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3, Randomized, Double-Blind Study Comparing Tedizolid Phosphate and Linezolid for Treatment of Ventilated Gram-Positive Hospital-Acquired or Ventilator-Associated Bacterial Pneumonia

Abstract: Background Hospital-acquired bacterial pneumonia (HABP) and ventilator-associated bacterial pneumonia (VABP) are associated with high mortality rates. We evaluated the efficacy and safety of tedizolid (administered as tedizolid phosphate) for treatment of gram-positive ventilated HABP/VABP. Methods In this randomized, noninferiority, double-blind, double-dummy, global phase 3 trial, patients were randomized 1:1 to receive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 34 publications
(32 reference statements)
0
12
0
2
Order By: Relevance
“…In this setting, the sterilization of lung airways with antimicrobial therapies cannot restore lung homeostasis, which can explain why the rates of treatment failure still reach 30% in the most recent studies evaluating treatment of HAP. 3 4 92…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, the sterilization of lung airways with antimicrobial therapies cannot restore lung homeostasis, which can explain why the rates of treatment failure still reach 30% in the most recent studies evaluating treatment of HAP. 3 4 92…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical studies in skin and skin-structure infections, in the first phase III clinical study in patients with hospital-acquired and ventilator-associated pneumonia, TDZ (200 mg/day for 6 days) was non-inferior to LNZ (600 mg twice daily for 10 days) in the primary outcome (28 days all-cause mortality). However, the non-inferiority of TDZ to LNZ was not established while comparing the secondary outcome (investigator-assessed clinical response at test of cure) [ 96 ]. There are no clear reasons for this discrepancy but the complexity of the disease and the subjectivity of defining “clinical cure” by clinicians can lead to this lack of consistency in the clinical outcomes.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…17 -36 Table 2 highlights the primary end point results of pivotal clinical trials that were conducted to assess their efficacy in the management of various disease states. 37 -86 Table 3 summarizes their contraindications, warnings and precaut...…”
Section: Antibiotics and Related Biologics Approved By The Fda From J...mentioning
confidence: 99%
“…73,74 Recently, in a phase 3 trial, tedizolid was shown to be noninferior to linezolid in the treatment of HABP/VABP for all-cause mortality at day 28; however, tedizolid failed to meet noninferiority for investigator-assessed clinical response at test of cure. 75 Tedizolid is an alternative option for the treatment of ABSSSIs but is not commonly used in clinical practice because of the availability of generic linezolid and other inexpensive options. Tedizolid has been used off-label with a varying degree of success in the treatment of prosthetic joint infections, osteomyelitis, central nervous system infections, mycobacterial infections, and pneumonia.…”
Section: Antibiotics and Related Biologics Approved By The Fda From J...mentioning
confidence: 99%